Underage commercial sex and criminal prosecutions: Who really are the victims? A Singapore perspective - MOHAN, S. Chandra (Institutional Knowledge at Singapore Management University, 2016)
In 2008 Singapore created a new offence under the Penal Code of under-aged commercial sex with any person below 18 years. The chapter discusses the many questions that arise from various cases and examines whether the prosecution and imprisonment of these offenders under the new law represent just desserts for the perpetrators of sexual exploitation, or whether they are merely examples of the overreach of the law, resulting in prosecution and imprisonment and the destruction of careers and families,resulting in perhaps multiple victims of the law.